Light, body and monsters: Interview with Rita Mátis - Pál, Gyöngyi (ARTCADIA, 2025)
Rita Mátis was born in Pécs in 1967. From 1981 to 1985, she studied at the Pécs Secondary School of Art, then from 1987 to 1992, she was a student of Ilona Keserü at the Faculty of Humanities of Janus Pannonius University, where she obtained her teaching degree. From 1992 to 1995, she studied under Gyula Konkoly at the JPTE Master School of Fine Arts. After completing this, she was awarded the title of "Master of Fine Arts." In 1995, she took part in a study trip to Paris, and in 1996, she stayed in Vienna as a KulturKontakt scholarship holder. In 2005, she spent a month and a half in Grödinge on a scholarship in Sweden. Between 2015 and 2016, she completed her doctoral studies at the Faculty of Arts of the University of Pécs. She spent July 2019 in Rome as a fine arts scholarship holder at the Hungarian Academy in Rome. She currently teaches as an associate professor at the MATE Rippl-Rónai Art Institute in Kaposvár.